Artificial Intelligence in Sports: Analyzing the Interplay Between Graffiti Art and Animated Art in Athletic Environments - Qingqing Hu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The integration of artificial intelligence (AI) in the realms of graffiti art and art animation has significantly influenced creative processes in various fields, including sports environments. This paper explores the dynamic interplay between AI-driven graffiti art and animation within the context of athletic environments, examining how these artistic forms enhance both aesthetic appeal and psychological engagement in sports settings. This integration not only enriches the visual experience associated with sports but also contributes to a deeper psychological connection with the audience, providing fresh insights into the cultural aspects of sports psychology. The evolving relationship between AI, graffiti art, and animation presents a valuable avenue for enhancing the spectator’s experience and athlete motivation, underscoring the potential of AI to transform traditional art forms into sports contexts.